The Multi-Site Order Fulfillment-Planning Model: A Global Corporation Case Study - Chen, Yin-Yann; ., Hsiao-Yao Fan (Journal of Social and Development Sciences, 2013)
A multi-site order fulfillment-planning model for the thin film transistor–liquid crystal display (TFT-LCD) panel industry is proposed. The order allocation problem is solved using a mathematical programming model considering practical characteristics, including product structures, customer preferences, alternative bill-of-material, and production constraints. A practical global corporation case in Taiwan will be employed to testify the feasibility of the proposed order fulfillment-planning model. Besides, the adaptability and comparison of different planning approaches in an environment of various market demands are discussed. Through the analysis of experiments, the proposed mathematical programming model is found to be better than the current popular method.